2019
DOI: 10.1002/hep.30405
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Nuclear Factor 4 Alpha Activation Is Essential for Termination of Liver Regeneration in Mice

Abstract: Hepatocyte nuclear factor 4 alpha (HNF4α) is critical for hepatic differentiation. Recent studies have highlighted its role in inhibition of hepatocyte proliferation and tumor suppression. However, the role of HNF4α in liver regeneration (LR) is not known. We hypothesized that hepatocytes modulate HNF4α activity when navigating between differentiated and proliferative states during LR. Western blotting analysis revealed a rapid decline in nuclear and cytoplasmic HNF4α protein levels, accompanied with decreased… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
109
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(121 citation statements)
references
References 51 publications
8
109
2
2
Order By: Relevance
“…Indeed, HNF4A was recently shown to support epithelial regeneration in the intestine in response to irradiation in a mouse genetic model [ 66 ]. Moreover, HNF4A is required for termination of liver regeneration, which requires inhibition of hepatocyte proliferation and reacquisition of their fully differentiated phenotype [ 67 , 68 , 69 ]. Accordingly, HNF4A is necessary to maintain hepatocyte identity in adult mice through regulation of liver-specific genes involved in lipid, glucose, and xenobiotic metabolism, as well as blood coagulation [ 67 , 70 , 71 ].…”
Section: Hnf4 Is a Cell-type Specific Tf Required For Cell Identitmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, HNF4A was recently shown to support epithelial regeneration in the intestine in response to irradiation in a mouse genetic model [ 66 ]. Moreover, HNF4A is required for termination of liver regeneration, which requires inhibition of hepatocyte proliferation and reacquisition of their fully differentiated phenotype [ 67 , 68 , 69 ]. Accordingly, HNF4A is necessary to maintain hepatocyte identity in adult mice through regulation of liver-specific genes involved in lipid, glucose, and xenobiotic metabolism, as well as blood coagulation [ 67 , 70 , 71 ].…”
Section: Hnf4 Is a Cell-type Specific Tf Required For Cell Identitmentioning
confidence: 99%
“…Modulation of HNF4 signaling through changes in expression or chromatin binding is not restricted to fluctuating physiological circumstances such as those linked to feeding but also occurs in pathophysiological situations. For instance, partial hepatectomy (PHx) of the mouse liver is accompanied by reduced chromatin accessibility as well as H3K27ac levels at HNF4A binding sites, decreased HNF4A genome occupancy, and diminished expression of HNF4A itself [ 68 , 69 ]. In line, reduced HNF4A expression and binding were identified as major contributors to the suppression of hepatocyte-specific genes and downregulation of liver biosynthetic functions during the liver repopulation process after acute injury in the Fumarylacetoacetate hydrolase ( Fah ) null mouse model [ 125 ].…”
Section: Hnf4 Loss Contributes To Loss Of Identity In Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Hepatocyte Nuclear Factor 1α (HNF1α) [16][17][18]. HNF4α is an established master regulator of induction and maintenance of the hepatic cell state [19,20]. HNF4α knockout mice exhibit severe hepatomegaly (enlarged liver) and steatosis [16,19].…”
Section: Introductionmentioning
confidence: 99%
“…(10) Hepatocyte nuclear factor-4 alpha (HNF4α) is an important transcription factor of the nuclear hormone receptor family, and is essential for maintaining a normal liver architecture. (11) Moreover, it also plays a crucial role in hepatic differentiation, metabolic function and formation of a polarized hepatic epithelium and cell-cell contact. (12) Moreover, as supported by similar research, (13,14) our previous study showed that HNF4α-overexpressing UMSCs (HNF4α-UMSCs) has signi cantly improved the differential status of hepatocyte-like cells by activating the expression of genes related to hepatocyte function.…”
Section: Introductionmentioning
confidence: 99%